Penerapan Model Pembelajaran Take and Give Terhadap Hasil Belajar Matematika Siswa - Putri Oktavia Ningsih; Yohana Satinem; Andriana Sofiarini (Journal of Elementary School (JOES), 2023)
This research was conducted to determine the mastery of mathematics learning outcomes after the implementation of the Take and Give learning model . The type of research used is quasi-experimental. The population of grade IV at SD Negeri 52 Lubuklinggau for the 2022/2023 academic year is 28 students and the sample taken is 28 students. Sampling using saturated sampling technique. Retrieval of data using test techniques. The data collected after being analyzed using the Z -test at a significant level = 0.05 was obtained (6.70) (1.64), so it can be concluded that the mathematics learning outcomes of class IV students at SD Negeri 52 Lubuklinggau after the Take and Give model was applied significant complete. Keyword: Mathematics, Application of the Take and Give Model